From Authenticity to Authority: Methods and Approaches of Intellectual History in Jonathan A.C. Brown’s Study of Hadith Canonization - Ahsan, Mohammad Nur (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
This paper explores the methods and approaches of intellectual history in the works of Jonathan A.C. Brown on the canonization of prophetic sources. Although his studies have sparked scholarly discussion in the following decades, the existing discussions have yet to involve his entire study of the topic and reconstructing his methods and approaches. This article examines Brown’s works on the canonization of ḥadīth texts to outline the methods and approaches to intellectual history that he applies. The close reading method is implemented in this article against Brown’s publications on the role of al-Dāraquṭnī, the canonization of al-Ṣaḥīḥayn, and al-Sunan by Ibn Mājah. Through the determination of the time and period of canonization and the explanation of the reasons behind the canonical status obtained by al-Ṣaḥīḥayn and al-Sunan li Ibn Mājah, Brown’s study on the canonization of prophetic sources in the Sunni community is a response to two problems left by Ignaz Goldziher. The use of methods and approaches in the field of intellectual history allows Brown to examine sources that are common in traditional hadith science in a new way of reading to determine spatial space, periodization, and the role of several agents from the intellectual community in the historical dynamics of hadith canon formation. Apart from criticism of the use of categories from Biblical canon studies to the phenomenon of hadith literature, Brown’s study shows the possibility of expanding the study beyond issues of source authenticity.